KEBERANIAN MENGAMBIL RISIKO MEMEDIASI PENGARUH EFIKASI DIRI DAN KEBUTUHAN AKAN PRESTASI TERHADAP NIAT BERWIRAUSAHA - Anggra Lutfi Aprilian Mustofa; Ni Wayan Ekawati (E-Jurnal Manajemen, 2017)
Problems such as unemployment, poverty and high population growth are a problem always faced by the State of Indonesia. In overcoming these problems, the role of entrepreneurs in creating employment in order to support the national economy. Therefore, this interesting research is conducted to find out how big the intention of entrepreneurship mahasisiwa non udayana university regular program. This research was conducted in Udayana University's non-regular study program. The number of samples used is 180 respondents, using probability sampling technique, especially Proportionate Stratified Random. The data that have been collected is processed by using path analysis technique (Path Analysis). The results of this study indicate that self efficacy and the need for achievement affect the intention of brwirausaha. However, the mediation variables of courage take the risk of no influence on the intention of entrepreneurship. In addition, the influence of indirect self-efficacy and the need for achievement does not occur because the value of the coefficient of direct relationship is greater than the value of indirect coefficient.